Functional Immune Cell Differences Associated With Low Vaccine Responses in Infants. (9th February 2016) - Pichichero, Michael E.; Casey, Janet R.; Almudevar, Anthony; Basha, Saleem; Surendran, Naveen; Kaur, Ravinder; Morris, Matthew; Livingstone, Alexandra M.; Mosmann, Tim R.
Abstract: Background.  We sought to understand why some children respond poorly to vaccinations in the first year of life. Methods.  A total of 499 children (6–36 months old) provided serum and peripheral blood mononuclear cell samples after their primary and booster vaccination. Vaccine antigen-specific antibody levels were analyzed with enzyme-linked immunosorbent assay, and frequency of memory B cells, functional T-cell responses, and antigen-presenting cell responses were assessed in peripheral blood mononuclear cell samples with flow cytometric analysis. Results.  Eleven percent of children were low vaccine responders, defined a priori as those with subprotective immunoglobulin G antibody levels to ≥66% of vaccines tested. Low vaccine responders generated fewer memory B cells, had reduced activation by CD4 + and CD8 + T cells on polyclonal stimulation, and displayed lower major histocompatibility complex II expression by antigen-presenting cells. Conclusions.  We conclude that subprotective vaccine responses in infants are associated with a distinct immunologic profile.